EFFECT OF POST MORTEM INTERVAL TOWARD Î’-TRYPTASE AND CHYMASE EXPRESSION OF ANAPHYLACTIC HEART MAST CELLS - Susilo, Imam; Putra, Bilqisthi Ari; Yudianto, Ahmad (Faculty of Vocational Studies, Universitas Airlangga, 2023)
Background: The effects of post mortem interval on tryptase levels are unclear and have been challenging to quantify due to limited and at times contradictory research. Purpose: Analyze the effects of Post Mortem Interval (PMI) due to anaphylactic shock on the expression of β-tryptase and mast cell chymase in the heart organ. Method: This type of research was an experimental study with a randomized block design (RBD) with the same subjects and a time series for 24 hours, using 5 (five) rabbits. The measurement of β-tryptase and chymase expression was based on immunohistochemical IRS (immunoreactive score) in the heart organs of rabbits experiencing anaphylactic shock sensitization and induction of anaphylactic shock using ovalbumin. Result: Based on the results of statistical tests using univariate analysis, there was a relationship between the length of death (post mortem interval) and the expression of mast cells β-Tryptase and cardiac chymase (p-value = 0.006) and chymase (p-value = 0.002) with (p-value <0.05). The effective test time with β-tryptase markers using cardiac organs was prone to long death time of 0 - 15 hours. The effective check-up time with chymase markers using the heart organ was at a long time of death of 9 hours. Conclusion: The results of the study showed that tryptase and chymase could be used as markers of anaphylactic shock.